Differences of physique and physical fitness among male South Korean elite national track and field athletes - Bong-ju, S.; Byoung-goo, K. (International Journal of Human Movement and Sports Sciences, 2017)
The aim of this study was to provide a detailed comparison of physique and physical fitness differences among Track and Field groups. The male athletes participating in this study consisted only of South Korean national track and field athletes. The Korean national athletes were divided into four groups (long-distance runner, sprinter, jumper, thrower). The long-distance runner group (n=7) consisted of three male marathoners and four male race walkers. The sprinter group (n=7) consisted of five male 100m athletes and two male hurdlers. The jumper group (n= 7) consisted of 2 male high jumpers, 2 male long jumpers, and 3 male pole vault athletes. The thrower group (n=8) consisted of 2 male shot put athletes, two male javelin throwers, 2 male discus throwers and 2 male hammer throwers. This study was designed to investigate the effects of physique (height, weight), muscular strength (grip strength), muscular endurance (push-ups, sit-ups), agility (side step), power (vertical jump), cardiopulmonary endurance (maximal oxygen uptake, Anaerobic Threshold %VO2max, rest heart rate), and flexibility (sit and reach). A one-way ANOVA was performed for the mean difference test among track and field athlete groups. A post hoc test method was conducted through the Scheffe Test. The results are as follows. The thrower athlete group showed significantly better results in weight, muscular strength (grip power) than the sprinter athlete group, long-distance runner group and the jumper athlete group. The long-distance runner group showed significantly better result in VO2max and AT (Anaerobic Threshold) than the sprinter group, thrower group and the jumper group. The sprinter group showed significantly better results in power (vertical jump) than the other three groups. There was no significant difference among the groups in the results for muscular endurance (push-up, sit-up), flexibility (sit and reach) and agility (side steps). In conclusion, the South Korean national long-distance runner group (VO2max: 72.6ml/kg/min, ATVO2max: 54ml/kg/min) was superior to the other three groups in cardiovascular endurance. The sprinter's group (vertical jump: 63.1cm) was superior to the other three groups in power. The thrower group (weight: 97kg, grip strength: 81kg) was superior to the other three groups in muscular strength and was heavier than the other groups. Korean national track & field athletes showed the characteristics of cardiovascular endurance, muscular strength, and power in a detailed analysis of items. No differences were found in muscular endurance, flexibility, and agility. Differences in physique and physical fitness among detail event groups of Korean national athletes were in accordance with previous studies. In future studies, the sample size should be increased to improve the reliability and validity of the study results.